2013
DOI: 10.1152/ajprenal.00464.2012
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of lithium-induced natriuresis and kaliuresis in P2Y2receptor knockout mice

Abstract: receptor activity and increased renal Na ϩ conservation. We hypothesized that P2Y2R KO mice would be less sensitive to lithiuminduced natriuresis and kaliuresis due to attenuated downregulation of one or more of the major renal Na ϩ or K ϩ transporter/channel proteins. KO and wild-type (WT) mice were fed a control or lithiumadded diet (40 mmol/kg food) for 14 days. Lithium-induced natriuresis and kaliuresis were significantly (ϳ25%) attenuated in KO mice. The subunits of the epithelial Na ϩ channel (ENaC) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…First, we and others (23,35) observed that genetic deletion of P2Y 2 receptor per se upregulates the protein abundance of NKCC2 in the medulla, and is associated with increased natriuresis in response to acute furosemide treatment. However, another group (13) using P2Y 2 receptor-knockout mice with a different genetic background, did not observe upregulation of NKCC2 protein or transepithelial transport compared with WT mice.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…First, we and others (23,35) observed that genetic deletion of P2Y 2 receptor per se upregulates the protein abundance of NKCC2 in the medulla, and is associated with increased natriuresis in response to acute furosemide treatment. However, another group (13) using P2Y 2 receptor-knockout mice with a different genetic background, did not observe upregulation of NKCC2 protein or transepithelial transport compared with WT mice.…”
Section: Discussionmentioning
confidence: 83%
“…Cortical and medullary tissue samples were processed separately as previously described (35,36) and shipped to Georgetown University for semiquantitative immunoblot analysis. Briefly, samples were prepared by homogenizing the frozen tissues in a buffer containing protease inhibitors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unless otherwise stated, mice were housed in groups in conventional plastic cages with bedding and regulated light-dark cycles and had free access to food and drinking water. NDI was induced by the administration of LiCl by the methods established in our laboratory [10,[14][15][16]. Age-matched adult male mice were randomly divided into four groups (five mice/group).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Based on this deduction, we posited that the same actions of extracellular nucleotides mediated by P2Y receptors may also contribute to the development of collecting duct resistance to AVP often seen in acquired nephrogenic diabetes insipidus (NDI), such as the one induced by chronic lithium administration for the treatment of bipolar disorder [11][12][13]. Accordingly, we demonstrated that genetic deletion of P2Y 2 receptor confers significant resistance for the development of lithium-induced NDI [14,15]. However, currently, there are no FDA-approved selective antagonists of the P2Y 2 receptor, thus limiting our in vivo studies using pharmacological approach on this receptor.…”
Section: Introductionmentioning
confidence: 96%